2007
DOI: 10.1074/jbc.m608726200
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Function in Mice Lacking the BK Channel α, β1, or β4 Subunits

Abstract: Large conductance voltage-and calcium-activated potassium (BK) channels are important for regulating many essential cellular functions, from neuronal action potential shape and firing rate to smooth muscle contractility. In amphibians, reptiles, and birds, BK channels mediate the intrinsic frequency tuning of the cochlear hair cell by an electrical resonance mechanism. In contrast, inner hair cells of the mammalian cochlea are extrinsically tuned by accessory structures of the cochlea. Nevertheless, BK channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 63 publications
3
79
0
Order By: Relevance
“…In these vertebrates, BK is colocalized with L-type Ca 2ϩ channels in presynaptic active zones (3) and is thus coupled to neurotransmitter release as described for the nerve muscle synapse (4,5). Although the onset of this channel during cochlear development in both mammals and non-mammals coincides with an increase in hearing sensitivity (6,7), its function is less clear in the former where hair cells are not frequency-tuned and studies report either the presence or the absence of hearing with the loss of BK (8,9). The BK channel has been localized to both the outer hair cells (OHC) (10) and inner hair cells (IHC) (7,(11)(12)(13) in mammals.…”
Section: Bkmentioning
confidence: 99%
See 1 more Smart Citation
“…In these vertebrates, BK is colocalized with L-type Ca 2ϩ channels in presynaptic active zones (3) and is thus coupled to neurotransmitter release as described for the nerve muscle synapse (4,5). Although the onset of this channel during cochlear development in both mammals and non-mammals coincides with an increase in hearing sensitivity (6,7), its function is less clear in the former where hair cells are not frequency-tuned and studies report either the presence or the absence of hearing with the loss of BK (8,9). The BK channel has been localized to both the outer hair cells (OHC) (10) and inner hair cells (IHC) (7,(11)(12)(13) in mammals.…”
Section: Bkmentioning
confidence: 99%
“…The BK channel has been localized to both the outer hair cells (OHC) (10) and inner hair cells (IHC) (7,(11)(12)(13) in mammals. However, unlike non-mammals, the BK channel appears in both synaptic and extrasynaptic sites near the apical end or neck of the IHC (9).…”
Section: Bkmentioning
confidence: 99%
“…BK channel proteins are homotetramers formed by BK α-subunits, which then associate with different β-or γ-subunits in a tissue-specific manner (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The α-subunit of the BK (K Ca 1.1) channel is encoded by the KCNMA1 gene, first discovered in Drosophila as the slowpoke mutation (dSlo) (23, 24), and later identified in mouse (mSlo1) and human (hSlo1) (25, 26).…”
mentioning
confidence: 99%
“…Taken together, these results demonstrate that the secretion of K ϩ requires and is likely mediated by KCa1.1 potassium channels localized to the apical membranes of striated and excretory duct cells in the mouse submandibular exocrine gland. salivary gland; potassium secretion; calcium-activated K channels; duct cells MAXI-K CHANNELS ARE ASSOCIATED with a diverse array of cellular functions including, for example, smooth muscle contractility (22,37), cell volume control (32,42), neuronal action potentials (26,27,39), hearing loss in cochlear hair cells (31,34), and K ϩ secretion by the renal tubules and the crypt cells of the distal colon (29,38). We have previously demonstrated that the K Ca 1.1 gene (also known as Kcnma1) encodes the maxi-K channel in the acinar cells of parotid and submandibular exocrine glands (32,33).…”
mentioning
confidence: 99%